2021
DOI: 10.1108/bfj-01-2021-0105
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound irradiation of grapes: effect on the anthocyanin profile of “Isabella” juice

Abstract: PurposeThe aim of this study was to evaluate the effect of ultrasound (US) treatment on the postharvest of “Isabella” grapes and the consistency of the obtained results regarding the composition of anthocyanins in grape juice over three successive harvest years using a combination of analytical techniques.Design/methodology/approachJuices produced from “Isabella” grapes sonicated for different durations (3, 5, 7 and 10 min) were analysed. The grapes were harvested and sonicated in 2013, 2014 and 2015, and each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…Zhang et al [31] reported that US could substantially improve the contents of free, esterified and insoluble-bound phenolics in mangoes. Similar results were obtained by Comarella et al [32] on “Isabella” grape and Li et al [33] on blueberry.…”
Section: Introductionsupporting
confidence: 87%
“…Zhang et al [31] reported that US could substantially improve the contents of free, esterified and insoluble-bound phenolics in mangoes. Similar results were obtained by Comarella et al [32] on “Isabella” grape and Li et al [33] on blueberry.…”
Section: Introductionsupporting
confidence: 87%
“…Therefore the color values of raw milk and treated milk were not statistically different [143] . In a more recent study, Comarella et al [35] noticed an increased concentration of monomeric anthocyanins in “Isabella” grape juice due to US irradiation because of the synergism between sonication time and temperature leading to increased release of bioactive compounds. They divulged that the free radical formation and mechanical perturbation could trigger the defense responses in plants activating secondary metabolism and stimulating the production of phenolic substances like anthocyanins and flavonoids, which could, in turn, improve the color properties of such products.…”
Section: Ultrasonication Applications On Color Profile Of Foodsmentioning
confidence: 99%
“…Ultrasonic irradiation treatment/pre-treatment application also ensures increased effectiveness of the succeeding process or unit operation to be applied, for instance, drying or cooking. In addition, it is widely used to increase the extraction of bioactive compounds from fruit/vegetables and all kinds of food by-products [128] , oil recovery from oil seeds plant [85] , bioethanol yield from lignocellulosic materials [90] , or alcoholic/nonalcoholic beverages processing [114] , [35] . Besides these, using ultrasonic irradiation alone can also significantly affect foods' physical and chemical properties [197] .…”
Section: Ultrasonication Applications On Color Profile Of Foodsmentioning
confidence: 99%
“…Los antioxidantes, compuestos fenólicos y polifenólicos totales del ACP tienen la capacidad de combatir el estrés oxidativo e inhibición de los radicales libres que causa enfermedades y envejecimiento prematuro a los seres humanos (Chinenye et al, 2020;Baena et al, 2021). Comarella et al (2021), reportó una mayor concentración de antocianinas monoméricas en el jugo de uva "Isabella" debido a la irradiación con US que causa sinergia entre el tiempo de sonicación y la temperatura que conduce a una mayor liberación de compuestos bioactivos, generando la formación de radicales libres y la perturbación mecánica que desencadenan las respuestas de defensa en las plantas activando el metabolismo secundario y estimulando la producción de sustancias fenólicas como antocianinas y flavonoides, que mejoraran las propiedades de color de dichos productos.…”
Section: Campo-veraunclassified